Cattle experimentally infected by Anaplasma marginale: Influence of splenectomy on disease pathogenesis, oxidative profile, and antioxidant status. (June 2016) - Doyle, Rovaina L.; França, Raqueli T.; Oliveira, Camila B.; Rezer, João F.P.; Klafke, Guilherme M.; Martins, João R.; Santos, Andrea P.; do Nascimento, Naíla C.; Mesick, Joanne B.; Lopes, Sonia T.A.; Leal, Daniela B.R.; Da Silva, Aleksandro S.; et al.
Abstract: Bovine anaplasmosis is caused by the obligate intraerythrocytic bacteria Anaplasma marginale. These bacteria are transmitted by tick species such as Rhipicephalus (Boophilus ) microplus, blood-sucking insects, and fomites (needles, clippers, and other blood contaminated equipment). During the acute phase of infection, animals may develop fever, anemia, jaundice, and hepatosplenomegaly. The aims of this study are to quantify the bacteremia by quantitative PCR in eight naïve calves experimentally infected by A. marginale [splenectomized (n = 4), and intact/non-splenectomized (n = 4)], and to correlate these findings with markers of oxidative stress on days 0, 8, 15, 21 and 23 post-infection. Complete blood counts (CBC) were performed in both groups. Lipid peroxidation was estimated by quantifying thiobarbituric acid reactive substances (TBARS); and non-enzymatic antioxidants were assessed by erythrocyte content of non-protein thiols (NPSH). There were no significant differences in complete blood counts (CBC) between the two groups. However, both groups had a slight decrease on packet cell volume (PCV), erythrocytes and hemoglobin concentration, as well as an increase in total leukocyte counts due to elevated lymphocytes when comparing pre and post-infection with A. marginale . Progressive increase on TBARS levels and concomitant decrease on NPSH content were observed in all animals, without significant differences between splenectomized and intact animals. A positive correlation between bacteremia and TBARS, and a negative correlation between bacteremia and NPSH were observed in both groups with higher correlation for NPSH in splenectomized animals. A negative correlation between TBARS and NPSH levels was observed in both groups indicating lipid peroxidation without a non-enzymatic antioxidant response. The results of experimental infection by A. marginale in cattle showed that bacteremia has an impact on lipid peroxidation regardless of the splenectomy. Highlights: Anaplasmosis is one of the most important tick-borne diseases in cattle Anaplasma marginale infection in cattle causes anemia, oxidative stress and antioxidant imbalance. High bacteremia is directly associated to lipid peroxidation. Reduction of non-enzymatic antioxidants in splenectomized animals.